CD36 initiates the secretory phenotype during the establishment of cellular senescence. (18th May 2018) - Chong, Mengyang; Yin, Tao; Chen, Rui; Xiang, Handan; Yuan, Lifeng; Ding, Yi; Pan, Christopher C; Tang, Zhen; Alexander, Peter B; Li, Qi‐Jing; Wang, Xiao‐Fan
Abstract: Cellular senescence is a unique cell fate characterized by stable proliferative arrest and the extensive production and secretion of various inflammatory proteins, a phenomenon known as the senescence‐associated secretory phenotype (SASP). The molecular mechanisms responsible for generating a SASP in response to senescent stimuli remain largely obscure. Here, using unbiased gene expression profiling, we discover that the scavenger receptor CD36 is rapidly upregulated in multiple cell types in response to replicative, oncogenic, and chemical senescent stimuli. Moreover, ectopic CD36 expression in dividing mammalian cells is sufficient to initiate the production of a large subset of the known SASP components via activation of canonical Src–p38–NF‐κB signaling, resulting in the onset of a full senescent state. The secretome is further shown to be ligand‐dependent, as amyloid‐beta (Aβ) is sufficient to drive CD36‐dependent NF‐κB and SASP activation. Finally, loss‐of‐function experiments revealed a strict requirement for CD36 in secretory molecule production during conventional senescence reprogramming. Taken together, these results uncover the Aβ–CD36–NF‐κB signaling axis as an important regulator of the senescent cell fate via induction of the SASP. Synopsis: In response to various senescence‐inducing stimuli, normal mammalian cells rapidly upregulate the scavenger receptor CD36. Amyloid beta‐dependent CD36 signaling then triggers NF‐κB pathway activation, resulting in the production and secretion of numerous inflammatory proteins known to comprise the senescence‐associated secretory phenotype. The multi‐ligand receptor CD36 is induced in multiple senescence contexts. Amyloid beta activates CD36 to stimulate NF‐κB‐dependent cytokine and chemokine production. Sustained secretory molecule production leads to the onset of a comprehensive senescent cell fate. Abstract : The scavenger receptor CD36 and its ligand amyloid beta trigger NF‐κB pathway activation and the acquisition of a senescence‐associated secretory phenotype (SASP) in response to various senescence‐inducing stimuli.